0
$\begingroup$

Let $k_1,k_2,\cdots,k_n,\cdots$ be a sequence of known positive numbers. Define $$ a_1:=k_1,\\ a_2:=C_2^2k_2+C_2^1k_1a_1,\\ a_3:=C_3^3k_3+C_3^2k_2a_1+C_3^1k_1a_2,\\ a_4:=C_4^4k_4+C_4^3k_3a_1+C_4^2k_2a_2+C_4^1k_1a_3,\\ \cdots\\ a_n:=C_n^nk_n+C_n^{n-1}k_{n-1}a_1+C_n^{n-2}k_{n-2}a_2+\cdots+C_n^1k_1a_{n-1}. $$ What is the general term formula for $a_n$?

$\endgroup$
  • 3
    $\begingroup$ Let $A(x) = \sum_{n=0}^\infty a_n x^n/n!$, where $a_0=1$, and let $K(x) = \sum_{n=1}^\infty k_n x^n/n!$. Then $A(x) = 1/(1-K(x))$. $\endgroup$ – Ira Gessel May 15 at 21:33
  • $\begingroup$ Could you please provide more details? I still can not get the general formula for $a_n$. Thank you very much! $\endgroup$ – Wenguang Zhao May 16 at 4:22
  • $\begingroup$ Expand $1/(1-K(x))= \sum_n K(x)^n$ by the multinomial theorem. See my answer to mathoverflow.net/questions/53384/…. $\endgroup$ – Ira Gessel May 16 at 5:10
  • $\begingroup$ Thanks very much! $\endgroup$ – Wenguang Zhao May 16 at 6:21

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.